PROPOSED INTEGRATED MARKETING COMMUNICATION STRATEGY TO INCREASE CONSUMER-BASED BRAND EQUITY FOR LIFEBUOY SOAP - Bianca Hediana; Satya Aditya Wibowo; Yudo Anggoro (Journal of Economic, Bussines and Accounting (COSTING), 2025)
This research delves into the revitalization of Lifebuoy's consumer-based brand equity by developing and implementing a comprehensive integrated marketing communication (IMC) strategy. The study addresses the brand's declining equity by conducting a thorough analysis of its internal and external environments. A mixed-methods research approach, encompassing both quantitative and qualitative data collection techniques, was employed to gain a deeper understanding of consumer behavior, preferences, and the competitive landscape. Key findings from the research indicate that Lifebuoy operates in a highly competitive market, facing intense rivalry from established brands like Biore, Dettol, and Nuvo. Consumer behavior is primarily driven by hygiene concerns, skin health, and affordability, with a growing emphasis on additional benefits. Despite its strong brand equity, product quality, and innovative offerings, Lifebuoy faces challenges in maintaining its market leadership. To address these challenges and revitalize the brand, a comprehensive IMC strategy is proposed. This strategy leverages a multi-channel approach, incorporating advertising, sales promotion, public relations, digital marketing, online marketing, mobile marketing, direct marketing, and event marketing. By effectively implementing this strategy, Lifebuoy can strengthen its brand equity, increase market share, and solidify its position as a leading antibacterial soap brand.